Relations between self-reported daily-life fatigue, hearing status and pupil dilation during a speech perception in noise task - Wang, Yang; Naylor, Graham; Kramer, Sophia E.; Zekveld, Adriana A.; Wendt, Dorothea; Ohlenforst, Barbara; Lunner, Thomas (Lippincott, Williams & Wilkins, 2018)
Objective: people with hearing impairment are likely to experience higher levels of fatigue due to effortful listening in daily communication. This hearing-related fatigue might not only constrain their work performance, but also result in withdrawal from major social roles. Therefore, it is important to understand the relationships between fatigue, listening effort, and hearing impairment, by examining the evidence from both subjective and objective measurements. The aim of the present study was to investigate these relationships by assessing subjectively measured daily-life fatigue (self-report questionnaires) and objectively measured listening effort (pupillometry) in both normally-hearing and hearing-impaired participants.